2021
DOI: 10.1108/ijshe-04-2020-0121
|View full text |Cite
|
Sign up to set email alerts
|

Wicked problems: university research topic convergence despite divergence in local educational and innovation policies

Abstract: Purpose This study aims to determine how sustainable development (SD) demands (according to the United Nations Economic Commission for Europe’s (UNECE) SD themes from 2005) are connected to the contents of education, research, development and innovation (RDI) in higher education institutions (HEI). Education and the RDI nexus may affect HEI’s capability to handle SD-related wicked problems and enhance their societal impact. Design/methodology/approach This paper examined SD-oriented curricula contents of two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…The most significant feature of the obtained results is multi-disciplinarity, which resonates with the often discussed role of higher education in addressing the wicked problems of the 21st century, including the sustainable development, innovation, and production of human capital for the contemporary economy and society [37][38][39]. A multidisciplinary approach to research and transboundary education is required to deal with these challenges to the modern society [40], which is especially valuable when dealing with crises, such as those encountered in the last five years in the EU-more specifically, with the massive inflow of migrants [41], COVID-related economic challenges [42], and other relevant issues.…”
Section: Resultsmentioning
confidence: 83%
“…The most significant feature of the obtained results is multi-disciplinarity, which resonates with the often discussed role of higher education in addressing the wicked problems of the 21st century, including the sustainable development, innovation, and production of human capital for the contemporary economy and society [37][38][39]. A multidisciplinary approach to research and transboundary education is required to deal with these challenges to the modern society [40], which is especially valuable when dealing with crises, such as those encountered in the last five years in the EU-more specifically, with the massive inflow of migrants [41], COVID-related economic challenges [42], and other relevant issues.…”
Section: Resultsmentioning
confidence: 83%
“…Finally, the yellow cluster includes curriculum-related issues. Here, for example, the areas of sustainability that are prioritized by the Chilean school curriculum [5], the content of curricula oriented to sustainable development [68], and the degree of curricular environmentalization in undergraduate courses at a Brazilian university [69] are addressed.…”
Section: Discussionmentioning
confidence: 99%
“…The studies have shown differences by discipline, while the mainstream seems to be multi- and transdisciplinarity, which points to combinations of SDGs (De Welde, 2015). The thin nexus between education and RDI and the scant research on transdisciplinarity are two major challenges met by those who attempt to solve complex wicked problems related to SD (Wals, 2014; Annala and Mäkinen, 2017; Greig and Priddle, 2019; Friman et al , 2021). According to Waas et al (2010), monodisciplinary research on SD is still needed, but its connections with sustainability are important.…”
Section: Theoretical Backgroundmentioning
confidence: 99%